Genetic variability and divergence in okra (Abelmoschus esculentus) (Current Horticulture, 2024)
An experiment comprising of 10 genotypes of okra {Abelmoschus esculentus (L) Moench} sown in RBD with three replications was  conducted during rainy season of 2019 and 2020 at Vegetable Research Farm, BUAT Banda. The genotypic coefficient of variation  (GCV) and phenotypic coefficient of variation (PCV) were highest for days to 50% germination and lowest for first flower, days to  50% flower, days to maturity, fruit length, fruit diameter, number of seeds/fruit, fruit yield/plant, fruit yield/plot and fruit yield (q/ha).  The heritability estimates were high for days to 50% germination, average fruit weight, number of fruits/plant, fruit yield/ plant and  fruit yield (q/ha) indicating that selection based on phenotypic performance would be more operative. The high heritability coupled  with high GAM was observed for days to 50% germination, average fruit weight and number of fruits/plant, indicating that additive  gene effect was more important. Based on D2 analysis, 19 genotypes were grouped into six clusters. The cluster I had seven genotypes  followed by cluster II and III with six and three genotypes respectively, while and remaining clusters were monogenotypic. The cluster  II recorded maximum intra cluster distance, followed by cluster I and clusters III. Maximum inter-cluster distance was observed  between cluster III and VI, followed by that between cluster III and IV and between cluster I and III, suggesting that genotypes  belonging to cluster III and VI, III and IV and I and III are more divergent than the rest of the clusters. Per cent character contribution  towards genetic divergence was maximum for fruit yield (q/ha), followed by average fruit weight, days to 50% germination, number  of seeds/fruit and fruit yield/plant showing selection of these characters. Apart from the above findings it can be concluded that,  selection and hybridization of genotypes from high divergent clusters III (Kashi Kranti, Hisar Naveen, P-8) and VI (Punjab Suhavani)  and cluster I (NDO-10, Azad Bhindi-1, Kashi Vibhuti, Arka Abhay, Kashi Vardan, Arka Anamika, Kashi Pragati) and cluster III (Kashi  Kranti, Hisar Naveen, P-8) are expected to yield potential F1s and transgressive for further exploitation.
Keywords: GCV; PCV; Heritability; Genetic Divergence